A Combination Analysis of IVIM-DWI Biomarkers and T2WI-Based Texture Features for Tumor Differentiation Grade of Cervical Squamous Cell Carcinoma. (17th March 2022) - Shi, Bin; Dong, Jiang-Ning; Zhang, Li-Xiang; Li, Cui-Ping; Gao, Fei; Li, Nai-Yu; Wang, Chuan-Bin; Fang, Xin; Wang, Pei-Pei
Abstract : Purpose . To explore the value of intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and texture analysis on T2-weighted imaging (T2WI) for evaluating pathological differentiation of cervical squamous cell carcinoma. Method . This retrospective study included a total of 138 patients with pathologically confirmed poor/moderate/well-differentiated (71/49/18) who underwent conventional MRI and IVIM-DWI scans. The values of ADC, D, D ∗, and f and 58 T2WI-based texture features (18 histogram features, 24 gray-level co-occurrence matrix features, and 16 gray-level run length matrix features) were obtained. Multiple comparison, correlation, and regression analyses were used. Results . For IVIM-DWI, the ADC, D, D ∗, and f were significantly different among the three groups (p < 0.05 ). ADC, D, and D ∗ were positively correlated with pathological differentiation ( r  = 0.262, 0.401, 0.401; p < 0.05 ), while the correlation was negative for f ( r  = −0.221; p < 0.05 ). The comparison of 52 parameters of texture analysis on T2WI reached statistically significant levels (p < 0.05 ). Multivariate logistic regression analysis incorporated significant IVIM-DWI, and texture features on T2WI showed good diagnostic performance both in the four differentiation groups (poorly vs. moderately, area under the curve(AUC) = 0.797; moderately vs. well, AUC = 0.954; poorly vs. moderately and well, AUC = 0.795; and well vs. moderately and poorly, AUC = 0.952). The AUCs of each parameters alone were smaller than that of each regression model (0.503∼0.684, 0.547∼0.805, 0.511∼0.712, and 0.636∼0.792, respectively; pairwise comparison of ROC curves between regression model and individual variables, p < 0.05 ). Conclusions . IVIM-DWI biomarkers and T2WI-based texture features had potential to evaluate the pathological differentiation of cervical squamous cell carcinoma. The combination of IVIM-DWI with texture analysis improved the predictive performance.